2022
DOI: 10.1101/2022.04.02.486242
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A comparison of feature selection methodologies and learning algorithms in the development of a DNA methylation-based telomere length estimator

Abstract: The field of epigenomics holds great promise in understanding and treating disease with advances in machine learning (ML) and artificial intelligence being vitally important in this pursuit. Increasingly, research now utilises DNA methylation measures at cytosine-guanine dinucleotides (CpG) to detect disease and estimate biological traits such as aging. Given the high dimensionality of DNA methylation data, feature-selection techniques are commonly employed to reduce dimensionality and identify the most import… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 85 publications
(119 reference statements)
2
11
0
Order By: Relevance
“…filtering by magnitude of correlation or strength of association) instead of, or in addition to elastic net [53][54][55][56][57][58][59][60]. Whereas the feature pre-selection here required arbitrary decisions on thresholds, other studies have found that feature reduction via PCA optimises DNAm predictors [36,37].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…filtering by magnitude of correlation or strength of association) instead of, or in addition to elastic net [53][54][55][56][57][58][59][60]. Whereas the feature pre-selection here required arbitrary decisions on thresholds, other studies have found that feature reduction via PCA optimises DNAm predictors [36,37].…”
Section: Discussionmentioning
confidence: 96%
“…Several studies have highlighted the benefits of feature pre-selection for elastic net [36,37]. Here, we performed preliminary analyses, including differently sized subsets of CpG sites as features in elastic net.…”
Section: Feature Pre-selectionmentioning
confidence: 99%
“…Several DNAm studies of age and age-related phenotypes have used pre-selection methods (e.g., filtering by magnitude of correlation or strength of association) instead of, or in addition to elastic net 3845 . Whereas the feature pre-selection here required arbitrary decisions on thresholds, other studies have found that feature reduction via PCA optimises DNAm predictors 46,47 .…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have highlighted the benefits of feature pre-selection for elastic net 46,47 . Here, we performed preliminary analyses, including differently sized subsets of CpG sites as features in elastic net.…”
Section: Feature Pre-selectionmentioning
confidence: 99%
“…There are many types of feature selection including filter, wrapper and embedded methods. Additionality, feature transformation methods such as PCA can be used to reduce the dimensionality of datahowever these methods do not necessarily yield an explicit set of features and can be less valuable in understanding how features drive a model's decision (Doherty et al, 2022). As such, in this study we have adopted a filter method (LGBM feature importance) to compare the impact of each featurethe importance scores can be used to rank each feature.…”
Section: Analysis Of Features Importancementioning
confidence: 99%